ANALISIS MANFAAT INSENTIF PAJAK PENGHASILAN DAN PENGARUHNYA PADA KEPATUHAN WAJIB PAJAK Studi tentang Kepuasan Wajib Pajak terhadap insentif pajak pada perusahaan PMA Agribisnis Tahun 2000 s.d 2007 - Sutrisno Ali; Bunasor Sanim; Harianto Harianto; Setiadi Djohar (Program Magister Akuntansi Unsyiah, 2011)
Tax incentives are demanded by both tax payers and government to facilitate the business climate in the right way. From the government point of view, tax incentives are government’s sacrifice to promote investments in the certain industry or locations; on the other hand, from taxpayer’s point of view, it is an opportunity to develop their business as more funds are available from less tax liabilities. Government should be careful to give tax incentives since target tax revenue has become larger and larger. On the other hand, taxpayers are skeptic with the tax incentives whether there are any benefits for their business. The answer to the skepticism depends on taxpayer’s satisfaction on the tax incentives received. Based on the result of this research to the agribusiness foreign investor’s samples, the degree of satisfaction from the tax incentives is varied. It depends on the type of tax incentive, business characteristic of tax payer and the countries of investors. In micro economics theory, satisfaction to a firm’s product usually leads to the loyalty to the product itself and furthermore leads to sales increasing. In line with the economic theory, tax payer’s satisfaction to a tax incentive will lead to the tax compliance and in a democratic country, the voluntary tax complience is the best foundation to increase tax collectibility.. This research noted that there are correlation between tax satisfaction to a tax incentive and taxpayer’s compliance. Keywords: Tax incentives, investment, tax satisfaction, voluntary tax complience